BEAM CHARACTERISTIC ANALYSIS OF VARIAN CLINAC 2100 ON 6 MV PHOTON MODE USING MONTE CARLO PRIMO SIMULATION - Timotius Manik, Josua
One of the main modalities in cancer treatment is radiotherapy, using ionizing radiation to distribute maximume dose at cancer target cells. Accurate dose calculation in treatment planning require the knowledge of the beams characteristic. This characteristics can be studied through a Monte Carlo (MC) simulation. In this study, a MC simulation was carried out using the PRIMO program with aims to analyze the characteristics of the Varian Clinac 2100 beams on 6 MV photon mode. Beams parameters used follow the default values provided in the program, such as initial electron energy of 5.4 MeV, energy FWHM 0 MeV, focal spot FWHM 0 cm and beam divergence 0o. The simulation is divided into four models (A to D) by varying the field size of 10 × 10 cm2, 20 × 20 cm2, 30 × 30 cm2 and 40 × 40 cm2. The analysis was carried out on the phase-space file (PSF) 1 and 2. PSF 1 position is at the downstream end of the upper parts of the linac, while PSF 2 located at lower parts of the linac. Simulation results for model A show that in PSF 1, the average angular distribution of photon beams is 10.74o and average energy is 1.18 MeV. In PSF 2, the average angular distribution is 2.62o and average energy is 1.50 MeV. Photon beams in the PSF 1 has a larger angular distribution than in the PSF 2, but the opposite occurs in the spectral distribution. Variation of field size shows that the photon beam in the PSF 2 have an average angular distribution of 4.56o, 6.31o, 6.66o and average energy of 1.40, 1.32, and 1.30 MeV respectively. Field size variation shows that at a larger field size, the beams will be scattered at a greater angle. The opposite occurs in the energy which gets smaller as the field size increases.